CHOCOLATE TART SUBSTITUTION WITH HEALTHY SNACKS IN FLOUR MILLET WITH RICH FIBER - Resma Hildarizla, Resma Hildarizla (Prosiding Pendidikan Teknik Boga Busana, 2020)
Many foods that only emphasizes taste and appearance without taking into account the nutritional content, especially the snack market that on average contain only energy such as, high-sugar, high carbohydrate content is also high in fat camlian market is usually low in fiber and minerals that are basically the two components are needed for the health of the human body. One of the much-loved snack is a kind of society that has been developed tart recipe called Chocolate Tart. Objective: The aim of this study was to determine consumer acceptance of chocolate tart with barley flour substitution study was conducted in laboratory Chem-Mix Primary. Reception of data obtained through a form filled out by. Results: The results showed that the panelists acceptance of the chocolate tart with flour substitution, fox, and taste At the level of public acceptance test the overall scale-free instrument to get an average high of 3.80 it is quite high and it can be concluded that the product of this development can be accepted by society. from the aspect of color, texture and, Conclusion: millet chocolate tart in flavor can be received due to a sense obtained unaffected by the substitution of barley flour. Keyword: reception, tart chcolate, barley flour